The organization of the future (San Francisco, Calif. : Jossey-Bass, 1997)
This book is divided into six parts: Shaping tomorrow's organizations; New models for working and organizing; Organizing for strategic advantage; Working and organizing in a wired world; Leading people in the organization of the future; and New definitions of organizational health.
Keywords: Organization; Innovation; Organizational change; Organizational innovation